TINGKAT KEMAMPUAN REFLEKSI DIRI DALAM PEMBELAJARAN MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TARUMANAGARA - Made Made Ayu Adesty Cahya Puspita (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Self-reflection is one of the important components needed by a learner to be able to develop himself. In medical education, self-reflection is useful in preparing students to become professional doctors and ready for lifelong learning. This study aims to determine the level of self-reflection ability in student learning at the Faculty of Medicine, Tarumanagara University by using a reflection in learning scale questionnaire. This research is descriptive quantitative with a cross-sectional approach. Respondents were 148 people with 74 students at the academic stage and 74 students at the professional stage. The results showed that the highest self-reflection ability in learning was owned by the academic stage respondents, was mostly at the level of the "ample" category (50%), followed by "maximum" (35.1%), "partial" (12.2%), and “restricted” (2.7%). While the results of research on self-reflection ability in learning are mostly owned by professional stage respondents, they are at the level of the " ample " category (63.5%), followed by "maximum" (28.4%), "partial" (8.1%), and “restricted” (0%). In addition, several factors have the potential to influence self-reflection such as age, gender, academic performance, motivation, and teacher responses. The conclusion of this research is that the level of self-reflection ability in student learning at the Faculty of Medicine, Tarumanagara University is at the “ample” category level.